Investigating the effect of plasma activated water on entomopathogenic nematodes under laboratory conditions - Pratik Doshi; Matej Klas; Stanislav Kyzek; Anna Zahoranová; Božena Šerá (Heliyon)
Entomopathogenic nematodes are currently being tested for their efficiency in controlling several insect pests. In recent years, non-thermal plasma has been investigated as a state-of-the-art technology for its disinfection/decontamination properties on the seed surface. In addition, it is also used to induce seed germination. In this investigation, the effect of plasma activated water (PAW) was tested on three EPN species, namely Steinernema feltiae Filipjev (1934), S. carpocapsae Weiser (1955), and Heterorhabditis bacteriophora Poinar (1976). Seven different PAW prepared at different treatment times, that is, (1s, 3s, 5s, 10s, 20s, 60s, 90s) were tested directly on the three selected nematode species. Distilled water was used as a control treatment (0s). In the case of H. bacteriophora, significantly higher mortality was observed in PAW preparation times of 5, 10, 20, 60 and 90s compared to the control. In the case of S. feltiae, significantly high mortality was observed for PAW preparation times of 10, 20, 60 and 90s. However, S. carpocapsae was found to have the least sensitivity against all PAW treatments, with a maximum mortality of 14 % (<20 %), indicating the potential synergy between PAW and EPNs. The possibility of combined treatments in the context of integrated pest management is presented and discussed.